Vitamin D supplementation for primary dysmenorrhea: a double-blind, randomized, placebo-controlled trial - Fatemeh Alsadat Rahnemaei; Ali Gholamrezaei; Maryam Afrakhteh; Farid Zayeri; Mohammad Reza Vafa; Arian Rashidi; Giti Ozgoli (Korean Society of Obstetrics and Gynecology, 2021)
Objective Recent studies have shown a possible association between vitamin D deficiency and the severity of primary dysmenorrhea. The present study aimed to investigate the effect of vitamin D supplementation on pain and systemic symptoms in patients with primary dysmenorrhea. Methods This double-blind, randomized, placebo-controlled trial was conducted on female students aged 18 to 32 years with primary dysmenorrhea and vitamin D deficiency (25 [OH]D <30 ng/mL). The participants (n=116) received either 50,000 IU of vitamin D3 (cholecalciferol) or placebo capsules on a weekly basis for eight consecutive weeks. The outcomes were pain intensity (scored 0 to 10), number of days with pain, number of consumed pain-relief medications (per day), and severity of systemic symptoms (fatigue, headache, nausea/vomiting, and diarrhea; total score of 0 to 12). Results Compared with baseline, our participants who received vitamin D experienced significant reductions in pain intensity (−1.0 and −1.5 score at weeks 4 and 8, P<0.001), the number of days with pain (−1.0 day at weeks 4 and 8, P<0.001), the number of consumed pain-relief medications (−1.0 at weeks 4 and 8, P<0.001), and systemic symptoms severity (−1.0 score at weeks 4 and 8, P<0.001). No significant improvements were observed in the placebo group in terms of these outcomes. Conclusion Vitamin D supplementation in women with primary dysmenorrhea and vitamin D deficiency could improve systemic symptoms and reduce pain intensity, the number of days with pain, and the need for consuming pain-relief medications.